“Madness in its Place”: Ecofeminism in Janet Frame’s Faces in the Water - Soon Seng, Foong (SARE: Southeast Asian Review of English, 2018)
In the twentieth century, placing madwomen in mental institutions was considered a civilised and progressive idea. Mental institutions were said to provide a soothing and calming environment for the patients in order to help them heal. However, Istina Mavet, the (mad)woman protagonist of New Zealand author Janet Frame’s Faces in the Water (1961), records her unforgettable experiences of being locked up at the Cliffhaven and Treecroft Mental Institutions for being “different”. The material space of the mental institutions influences Istina’s emotions and further distresses her. The aesthetic space of the mental establishment is superseded by its oppressive material space, which facilitates containment and exercises control over its female inmates. Hence, the healing process serves as a form of punishment to inmates. The spatial separation of the madwomen in the mental institution mirrors their patriarchal oppression. The comfort of the patients is pushed aside and their natural surroundings ignored. This paper adopts the new materialism approach as a complement to its ecofeminist perspective. It examines the “healing spaces” that have ironically affected the inmates’ mental well-being and disrupted the recovery process. It argues that although Istina is labelled a “madwoman,” she challenges the notion of “sanity” by displaying a sense of realism in her narration and by using it as a strategy for survival. Madness is therefore perceived as part of her “landscape” to aid her identity construction.